Voices of "Protest Archeology": Latin American Social Archeology: A Bibliometric Analysis of Boletín de Antropología Americana (1980-2012) - Núñez-Cortés, Yajaira (2019)
Boletín de Antropología Americana, published between 1980 and 2012 by the Instituto Panamericano de Geografía e Historia in Mexico, was the key media to discuss about the Latin American Social Archeology (ASL, in Spanish) movement. The scope of this theoretical model is analyzed through basic bibliometric analysis that allows to estimate the preponderance and persistence of the model over time, its main exponents, production at a theoretical level and its empirical level applications. The data show that the largest number of ASL articles was centered between 1980 and 1994, with an emphasis on Mexican authors and cases, with a more theoretical than methodological development and with a lower representation of case studies.